Compassionate use of Pulmonary Vasodilators in Acute Severe Hypoxic Respiratory Failure due to COVID-19. (August 2022) - Matthews, Lewis; Baker, Laurence; Ferrari, Matteo; Sanchez, Weronika; Pappachan, John; Grocott, Mike PW; Dushianthan, Ahilanandan; ,
Background: There have been over 200 million cases and 4.4 million deaths from COVID-19 worldwide. Despite the lack of robust evidence one potential treatment for COVID-19 associated severe hypoxaemia is inhaled pulmonary vasodilator (IPVD) therapy, using either nitric oxide (iNO) or prostaglandins. We describe the implementation of, and outcomes from, a protocol using IPVDs in a cohort of patients with severe COVID-19 associated respiratory failure receiving maximal conventional support. Methods: Prospectively collected data from adult patients with SARS-CoV-2 admitted to the intensive care unit (ICU) at a large teaching hospital were analysed for the period 14 th March 2020 - 11 th February 2021. An IPVD was considered if the PaO2 /FiO2 (PF) ratio was less than 13.3kPa despite maximal conventional therapy. Nitric oxide was commenced at 20ppm and titrated to response. If oxygenation improved Iloprost nebulisers were commenced and iNO weaned. The primary outcome was percentage changes in PF ratio and Alveolar-arterial (A-a) gradient. Results: Fifty-nine patients received IPVD therapy during the study period. The median PF ratio before IPVD therapy was commenced was 11.33kPa (9.93-12.91). Patients receiving an IPVD had a lower PF ratio (14.37 vs. 16.37kPa, p = 0.002) and higher APACHE-II score (17 vs. 13, p = 0.028) at ICU admission. At 72 hours after initiating an IPVD the median improvement in PF ratio was 33.9% (-4.3-84.1). At 72 hours changes in PF ratio (70.8 vs. −4.1%, p < 0.001) and reduction in A-a gradient (44.7 vs. 14.8%, p < 0.001) differed significantly between survivors (n = 33) and non-survivors (n = 26). Conclusions: The response to IPVDs in patients with COVID-19 associated acute hypoxic respiratory failure differed significantly between survivors and non-survivors. Both iNO and prostaglandins may offer therapeutic options for patients with severe refractory hypoxaemia due to COVID-19. The use of inhaled prostaglandins, and iNO where feasible, should be studied in adequately powered prospective randomised trials.